PERANCANGAN DAN PEMBUATAN SISTEM INFORMASI PARIWISATA DI MANGGARAI NTT STUDI KASUS RUMAH ADAT MANGGARAI BERBASIS WEBSITE - Mesach, Maria Nathalia; Fauziyah, Fauziyah; Whendasmoro, Raditya Galih (LPPM Universitas Bina Bangsa, 2023)
Tuition The Mbaru Niang, Mbaru Wunut and Mbaru Gendang Traditional Houses are traditional houses as well as historic places in Manggarai Regency, East Nusa Tenggara. Currently, information related to traditional houses is not well obtained so that potential tourists who want to find information related to traditional houses must visit the location directly, as well as services in ticket transactions for traditional houses are still carried out manually in the form of paper which can cause queues and paper waste around the area. tour. From the description of the problems that occurred, a Tourism Information System was designed and built in Manggarai NTT Case Study of Website-Based Manggarai Traditional Houses which is expected to be able to solve existing problems also in conducting tourist assessments in the form of ratings related to tourist attractions. In the design and manufacture of tourism information systems, Unified Modeling Language (UML), User Interface (UI), Black Box Testing is used. Tourism Information System in Manggarai NTT Case Study of Website-Based Manggarai Traditional House uses the PHP and MySQL programming languages as its database. The method used in completing this thesis is the interview method, the observation method and the method of literature study, design and testing. Which aims to provide information services to prospective tourists who need this information. After designing and manufacturing, it is necessary to know whether the application is running properly. The results of testing this information system using the Black Box which produces 12 valid test cases